2021
DOI: 10.3390/molecules26237221
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on the Halo- and Cyano-Trifluoromethylation of Alkenes and Alkynes

Abstract: Incorporation of fluorine into organic molecules is a well-established strategy in the design of advanced materials, agrochemicals, and pharmaceuticals. Among numerous modern synthetic approaches, functionalization of unsaturated bonds with simultaneous addition of trifluoromethyl group along with other substituents is currently one of the most attractive methods undergoing wide-ranging development. In this review article, we discuss the most significant contributions made in this area during the last decade (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 118 publications
0
9
0
Order By: Relevance
“…The simultaneous addition of trifluoromethyl and cyano groups onto carbon-carbon double and triple bonds is a widely developed strategy of modern organic syntheses. In 2021, Han [63] et al reported the recent advances on the halo-and cyanotrifluoromethylation of alkenes and alkynes summarizing the most significant contributions made in this area until 2021. Therefore, this chapter discusses only applications not included in this report.…”
Section: Cyanotrifluoromethylation Reactionsmentioning
confidence: 99%
“…The simultaneous addition of trifluoromethyl and cyano groups onto carbon-carbon double and triple bonds is a widely developed strategy of modern organic syntheses. In 2021, Han [63] et al reported the recent advances on the halo-and cyanotrifluoromethylation of alkenes and alkynes summarizing the most significant contributions made in this area until 2021. Therefore, this chapter discusses only applications not included in this report.…”
Section: Cyanotrifluoromethylation Reactionsmentioning
confidence: 99%
“…[11][12][13] Considering the importance of carbon-carbon bond-forming reactions in organic synthesis, carbotrifluoromethylations (Scheme 3) are worth more attention (currently, only aryltrifluoromethylation has an extensive literature). Because of the pseudohalogen nature of the nitrile group, cyanotrifluoromethylations [30] were omitted on Scheme 3.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[12] Furthermore, although many related reviews have been published after 2015, almost all of them are short reviews, [13] personal accounts, [14] or cover only specific topic such as photochemical reactions [15] and halo-trifluoromethylations. [16] Among the various difunctionalizative trifluoromethylation reactions, this review focuses on those accompanied by the formation of polar CÀ heteroatom (O, N, S, Se, B) or CÀ H bonds, as they provide useful CF 3 -substituted building blocks. Moreover, we aim to systematically map the reported variants of such trifluoromethylations, taking a bird's eye view of reaction conditions, modes, and mechanisms to identify the related evolution trends and future prospects.…”
Section: Introductionmentioning
confidence: 99%